Γδ T Cells Mediate Angiotensin II-Induced Hypertension and Vascular Injury. Issue 22 (30th May 2017) - Caillon, Antoine; Mian, Muhammad Oneeb Rehman; Fraulob-Aquino, Julio C.; Huo, Ku-Geng; Barhoumi, Tlili; Ouerd, Sofiane; Sinnaeve, Peter R.; Paradis, Pierre; Schiffrin, Ernesto L.
Abstract : Background: Innate antigen-presenting cells and adaptive immune T cells have been implicated in the development of hypertension. However, the T-lymphocyte subsets involved in the pathophysiology of hypertension remain unclear. A small subset of innate-like T cells expressing the γδ T cell receptor (TCR) rather than the αβ TCR could play a role in the initiation of the immune response in hypertension. We aimed to determine whether angiotensin (Ang) II caused kinetic changes in γδ T cells; deficiency in γδ T cells blunted Ang II-induced hypertension, vascular injury, and T-cell activation; and γδ T cells are associated with human hypertension. Methods: Male C57BL/6 wild-type and Tcrδ −/− mice, which are devoid of γδ T cells, or wild-type mice injected IP with control isotype IgG or γδ T cell-depleting antibodies, were infused or not with Ang II for 3, 7, or 14 days. T-cell profiling was determined by flow cytometry, systolic blood pressure (SBP) by telemetry, and mesentery artery endothelial function by pressurized myography. TCR γ constant region gene expression levels and clinical data of a whole blood gene expression microarray study, including normotensive and hypertensive subjects, were used to demonstrate an association between γδ T cells and SBP. Results: Seven- and 14-day Ang II infusion increased γδ T-cell numbers and activation in the spleen of wild-type mice ( P <0.05). Fourteen days of Ang II infusion increased SBP ( P <0.01) and decreased mesenteric artery endothelial function ( P <0.01) in wild-type mice, both of which were abrogated in Tcrδ −/− mice ( P <0.01). Anti-TCRγδ antibody-induced γδ T-cell depletion blunted Ang II-induced SBP rise and endothelial dysfunction ( P <0.05), compared with isotype antibody-treated Ang II-infused mice. Ang II-induced T-cell activation in the spleen and perivascular adipose tissue was blunted in Tcrδ −/− mice ( P <0.01). In humans, the association between SBP and γδ T cells was demonstrated by a multiple linear regression model integrating whole blood TCR γ constant region gene expression levels and age and sex ( R 2 =0.12, P <1×10 -6 ). Conclusions: γδ T cells mediate Ang II-induced SBP elevation, vascular injury, and T-cell activation in mice. γδ T cells might contribute to the development of hypertension in humans. Abstract : Supplemental Digital Content is available in the text.